1993
DOI: 10.4098/at.arch.93-18
|View full text |Cite
|
Sign up to set email alerts
|

Rodent population dynamics in a primeval deciduous forest (Białowieża National Park) in relation to weather, seed crop, and predation

Abstract: dynamics in a primeval deciduous forest (Białowieża National Park) in relation to weather, seed crop, and predation. Acta theriol. 38: 199 -232. (Schreber, 1780) and yellow-necked mice Apodemus flavicollis (Melchior, 1834) were studied in 1959 -1991 in the pristine mature forest dominated by hornbeam Carpinus betulus and oak Quercus robur in Białowieża National Park (eastern Poland). The whole 33-year series, and particularly the detailed data from 1971 -1991, were related to weather data and seed crop o f ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
337
3
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(362 citation statements)
references
References 50 publications
20
337
3
2
Order By: Relevance
“…Seasonal and multiannual fluctuations in population number were described by various authors in A. flavicollis from the Białowieża National Park (Adamczewska 1961, Grodziński et al 1966, Wójcik and Wołk 1985, Wołk and Kozłowski 1989. Pucek et al (1993) found that the extraordinarily high population numbers (outbreaks) in A. flavicollis occurred in 1977, 1983 and 1990 -one year after the mast (synchronous seed crop of oak, hornbeam, and maple) and was followed by rapid decline of numbers (crashes). All other years were characterized by intermediate abundance of mice.…”
Section: Introductionmentioning
confidence: 96%
“…Seasonal and multiannual fluctuations in population number were described by various authors in A. flavicollis from the Białowieża National Park (Adamczewska 1961, Grodziński et al 1966, Wójcik and Wołk 1985, Wołk and Kozłowski 1989. Pucek et al (1993) found that the extraordinarily high population numbers (outbreaks) in A. flavicollis occurred in 1977, 1983 and 1990 -one year after the mast (synchronous seed crop of oak, hornbeam, and maple) and was followed by rapid decline of numbers (crashes). All other years were characterized by intermediate abundance of mice.…”
Section: Introductionmentioning
confidence: 96%
“…Large irregular seed crops represent an important pulsed resource for birds, insects and mammals (Jensen 1982, Pucek et al 1993, Fitzgerald et al 1996, Pech et al 1999, Choquenot and Ruscoe 2000. In New Zealand, these high seedfall events result in a cascade of responses by both native birds and insects, and introduced mammals (Ruscoe et al 2005b, Kelly et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, the Nothofagus/Mus system is a Southern Hemisphere analogue of Northern Hemisphere systems involving 168 New Zealand Journal of Zoology, 2004, Vol. 31 masting trees and seed predators (e.g., crossbill (Loxia curvirostris) breed throughout winter when conifers mast (Newton 1972cited Caughley & Sinclair 1994; Peromyscus and Tamias in North America respond numerically to masting of Quercus (Ostfeld et al 1996;Wolff 1996); Apodemus and Clethrionomys in Europe respond to masting of Quercus, Acer, and Carpinus (Flowerdew 1973;Jensen 1982;Hansson 1984;Pucek et al 1993)). …”
Section: Introductionmentioning
confidence: 99%